Air pollutants and hospital admission due to pneumonia in children: a time series analysis - Souza,Laís Salgado Vieira de (2016)
Summary Objective: The aim of this study was to estimate the association between expo sure to air pollutants and hospitalization for pneumonia among children in a medium-sized city located in the sugar cane plantation region of São Paulo State. Methods: An ecological time-series study was conducted with daily data of hospi talization for pneumonia including children aged 10 years or younger living in Ar araquara, state of São Paulo, from January 1st, 2010, to November 30th, 2012. To es timate the association between hospitalization due to pneumonia and particulate pollutants with aerodynamic diameter less than 10 µm, nitrogen dioxide and ozone, relative risks for hospitalization according to a generalized additive model of Pois son regression, with Lags of up to five days, were calculated. A percentage increase (PI) was obtained for relative risk (IRR - increase on relative risk) of hospitalization at each 10 µg/m3 increment in each air pollutants adjusted for the remaining. Results: A total of 234 hospitalizations were recorded during these three years. There was a strong association between hospitalization and PM10 and NO2. The PI in relative risk was 15% to PM10 in Lag 0 and 7% points in Lag 1 for NO2. Conclusion: There was evidence of the action of air pollutants on hospitaliza tion for pneumonia in a medium-sized city located in a region affected by air pollution from sugarcane burning and the data presented here provide subsi dies for the implementation of public policies aiming to decrease this risk.